Dignity and the Organization 2016
DOI: 10.1057/978-1-137-55562-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Office Design and Dignity at Work in the Knowledge Economy

Abstract: SUMMARYThe current chapter looks at a grossly overlooked aspect affecting employee dignity in the workplace -the physical environment. While the knowledge economy has grown tremendously in the last four decades, researchers have not paid much attention to the new needs of the physical workspace despite the fact that office buildings represent the second largest financial overhead after human resource. At the same time, the physical space is a critical element in the organization of the processes, activities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The analysis of the received articles indicated what issues related to dignity in gainful employment were addressed in them . Nikolaeva and Dello Russo (2017) found that physical environment (office structure and layout, office decor and ergonomic aspects of design) as an aspect affecting dignity at work is grossly overlooked in the literature . Proper shaping of these elements can positively affect employees' physical and mental well-being, job satisfaction, team cohesion, and productivity .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis of the received articles indicated what issues related to dignity in gainful employment were addressed in them . Nikolaeva and Dello Russo (2017) found that physical environment (office structure and layout, office decor and ergonomic aspects of design) as an aspect affecting dignity at work is grossly overlooked in the literature . Proper shaping of these elements can positively affect employees' physical and mental well-being, job satisfaction, team cohesion, and productivity .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most notable are the flexibility of the space and the facilitation of collaboration in a work market which increasingly demands teamwork (Zahn, 1991;Vischer, 1999;Pinder et al, 2009;van Duinkerken and MacDonald, 2013). Still, a considerable body of research has shown disadvantages to shared offices such as increased noise and distraction (Hedge, 1982) and employees are seldom consulted about their implementation (Nikolaeva and Russo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Benefits, such as flexible use of space and facilitation of collaboration, support the adoption of shared office space within organizations ( vanDuinkerken and MacDonald, 2013 ); in contrast, others argue that the increase in noise and distraction, and a reduction of autonomy are considerable disadvantages ( Kim and de Dear, 2013 ; Nikolaeva and Dello Russo, 2017 ). A recent review found that a shared office workspace could have negative effects on the health and wellbeing of workers ( Richardson et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%